Ground shaking mapping for a scenario earthquake considering effects of geological conditios a case study for the 1995 Hyogo-ken Nanbu, Japan earthquake. - Fujimoto, Kazuo (Earthquake engineering & structural dynamics.)
In order to examine the applicability of ground shaking mapping techniques to a near field earthquake, a peak ground velocity map of the 1995 Hyogo-ken Nanbu, Japan earthquake computed from seismic zoning methods that consider the effects of geological conditions is compared with the actual observed intensity map. When computing the ground shaking map, the site amplification at each site is calculated in terms of the average shear wave velocity of the ground estimated from the corresponding geomorphological conditions. This map shows a relatively good agreement with the observed intensity map. However, the computations provide smaller values for certain disastrous areas of the earthquake, where the effects on ground motion of a deep, irregular underground structure have been reported. The effect of such structures on site response is examined implementing 2D FEM analyses, thereby being also incorporated into the method. Results considering the effect of the irregular underground structure show better agreement with the observed intensity map.